In Silico Simulation of Porous Geometry-Guided Diffusion for Drug-Coated Tissue Engineering Scaffold Design - Eyad Awad; Matthew Bedding-Tyrrell; Alberto Coccarelli; Feihu Zhao (Organoids)
Recent research works have shown the effect of nutrient concentration on cell activity, such as proliferation and differentiation. In 3D cell culture, the impact of scaffold geometry, including pore size, strut diameter, and pore shape, on the concentration gradient within scaffolds under two different loading conditions—constant fluid perfusion and non-fluid perfusion—in a perfusion bioreactor is investigated by developing an in silico model of scaffolds. In this study, both triply periodic minimal surface (TPMS) (with gyroid struts) and non-TPMS (with cubic and spherical pores) scaffolds were investigated. Two types of criteria are applied to the scaffolds: static and perfusion culture conditions. In a static environment, the scaffold in a perfusion bioreactor is loaded with a fluid velocity of <semantics>0 mm/s</semantics>, whereas in a dynamic environment, perfusion flow with a velocity of 1 mm/s is applied. The results of in silico simulation indicate that the concentration gradient within the scaffold is significantly influenced by pore size, strut diameter, pore shape, and fluid flow, which in turn affects the diffusion rate during drug delivery.